Non-invasive grading of aortic regurgitation by Doppler ultrasonography. Issue 3 (March 1986) - Hoffmann, A; Pfisterer, M; Stulz, P; Schmitt, H E; Burkart, F; Burckhardt, D
Abstract : Doppler ultrasound without concomitant echocardiographic imaging was used to grade isolated aortic regurgitation in 21 patients. The severity of aortic regurgitation was subsequently graded (from 0 to IV) angiographically. A 2 MHz continuous wave Doppler transducer was placed over the apex of the heart and the beam was aimed parallel to the mitral flow by means of acoustic guidance. Mitral pressure half time was calculated from the analogue maximum velocity tracing and it was less than or equal to 60 ms in 10 controls; 50-120 ms in five patients with grade II, 120-160 ms in nine patients with grade III, and greater than or equal to 160 ms in seven patients with grade IV aortic regurgitation. These results indicate that a semi-quantitative grading of aortic regurgitation may be obtained non-invasively with non-imaging Doppler ultrasonography in patients without concomitant mitral valve disease.